Types of Accidents and Causes of Their Occurrence in Outdoor Sports: A Conceptual Review - Erdoğan EKİNCİ (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
Accidents in outdoor sports typically arise from athletes' carelessness, inexperience, use of inappropriate equipment, or natural elements. These accidents can result in injuries, illnesses, or even death. Therefore, receiving proper training, adhering to safety regulations, and using appropriate equipment are crucial for outdoor sports activities. Additionally, being aware of the inherent risks in nature and taking the necessary precautions can help prevent accidents. This research aims to systematically identify the types of accidents that occur in outdoor sports. In this context, the study seeks to examine the causes and consequences of common types of accidents such as drowning, dehydration, poisoning, burn injuries, fires, hypothermia and frostbite, natural disasters, sunstroke and sunburn, wild animal attacks, and high-altitude sickness, as well as the measures participants should take to prevent these incidents. Outdoor sports, while exciting and enjoyable, also entail various risks. These risks include drowning, dehydration, poisoning, burn injuries, fires, hypothermia and frostbite, natural disasters, sunstroke, wild animal attacks, and high-altitude sickness. Consequently, it can be said that participants in outdoor sports activities are exposed to a range of risks. These risks necessitate that those interested in outdoor sports take appropriate precautions and prioritize safety. It is essential for participants to receive training suitable for their level of experience, use safety equipment correctly, and strictly adhere to safety rules, as these practices play a significant role in mitigating potential risks.